Efficacy of low-level laser therapy in pain relief during orthodontic treatment: Protocol for a systematic review and meta-analysis - Cintia Ronchi Lemos; Daniela Bianchini Orlandi; Anna Carolina Pereira Thimoteo; Helena Polmann; Patrícia Pauletto; Cristine Miron Stefani; Eliete Neves Silva Guerra; Carlos Flores-Mir; Graziela De Luca Canto (PLoS ONE, 2026)
Introduction Patient adherence to orthodontic treatment depends on comfort, absence of pain, and improved quality of life. Pain and discomfort from procedures like interproximal separation or appliance activation are often underestimated by professionals. Low-level laser therapy, with minimal side effects, shows potential for pain relief in orthodontics, though its efficacy remains uncertain. Objectives To investigate the efficacy of low-level laser therapy in controlling pain in orthodontic patients. Methods A systematic review of randomized controlled trials with orthodontic patients assessing low-level laser therapy will be done. Studies with specific treatments, such as hybrid orthodontics with skeletal anchorage or intermaxillary elastics, will be excluded. The intervention will compare low-level laser therapy alone versus sham therapy, no treatment, or other interventions. No restrictions will apply regarding publication date, language, or patient age. Primary outcomes will be pain; secondary outcomes will be quality of life and adverse effects. Searches will be performed in Cochrane, Embase, LILACS, MEDLINE (via PubMed), and Scopus, plus gray literature (Google Scholar, ProQuest), reference lists, expert consultations, and ClinicalTrials.gov. Retrieved records will be merged in a reference manager, with duplicates removed, and imported into LASER AI software. Calibrated authors will independently select studies in two phases: title/abstract screening and full-text screening. Included studies will undergo narrative synthesis, and, if sufficiently homogeneous, meta-analysis. Risk of bias will be assessed with RoB 2, and certainty of evidence graded with GRADE.